HERMENEUTIKA PAUL RICOEUR DAN PENERAPANNYA PADA PEMAKNAAN SIMBOL DALAM ROMAN “RAFILUS” KARYA BUDI DARMA - Indraningsih Indraningsih (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2011)
Hermeneutics requires a creative interpretation. Let a symbol are interpreted as a riddle (enigma), but with such beginning, the symbol show a meaning, giving its shape in a systematic and autonomous thinking. The thought which starts from the symbol contains two things: reflection and speculation. Reflection is demythologization, namely reduction of the myth becomes an allegory (allegory). Reflective thought is in disagreement with speculative thought which wants to save the symbol and consider the preferment.The work of Budi Darma, Rafilus romance, can be understood by the evil symbols of Ricoeur. An understanding of meaning by using such crime symbols will generate a reflective and speculative thinking. According to Ricoeur, there are three symbols of crime which are symbolically expressed through language; those are defilement, sin and guilt.Keywords: hermeneutics, symbolic, creative interpretation